Safe and Sufficient Glycemic Control by Using a Digital Clinical Decision Support System for Patients With Type 2 Diabetes in a Routine Setting on General Hospital Wards - Lichtenegger, Katharina M.; Aberer, Felix; Tuca, Alexandru C.; Donsa, Klaus; Höll, Bernhard; Schaupp, Lukas; Plank, Johannes; Beck, Peter; Fruhwald, Friedrich M; Kamolz, Lars-Peter; Pieber, Thomas R.; Mader, Julia K. (Journal of diabetes science and technology, 2021)
The aim was to investigate the applicability of a clinical decision support system in a real-world inpatient setting for patients with type 2 diabetes on general hospital wards. A total of 150 patients with type 2 diabetes requiring subcutaneous insulin therapy were treated with basal-bolus insulin therapy guided by a decision support system (GlucoTab) providing automated workflow tasks and suggestions for insulin dosing to health care professionals. By using the system, a mean daily blood glucose (BG) of 159 ± 32 mg/dL was achieved. 68.8% of measurements were in the target range (70 to <180 mg/dL). The percentage of BG values <40, <70, and ≥300 mg/dL was 0.02%, 2.2%, and 2.3%, respectively. Health care professionals’ adherence to suggested insulin doses and workflow tasks was high (>93% and 91%, respectively). The decision support system facilitates safe and efficacious inpatient diabetes care by standardizing treatment workflow and providing decision support for basal-bolus insulin dosing.